Introduction to verification of the GOHAI instrument for measuring - Popović, Željka V; Gajić, Ivanka; Obradović-Đuričić, Kosovka; Milošević, Dragoslav P (Vojnosanitetski pregled, 2016)
Abstract Background/Aim. Quality of life related to health should be seen as a multidimensional concept that, in addition to the physical symptoms associated with a disease and treatment, should include physical, psychological and social functioning of a person. The primary objective of this study was to use the Serbian preliminary version of the Geriatric Oral Health Assessment Index (GOHAI) questionnaire in oder to examine the consistency, reliability and stability, as well as an introduction to the verification tool. Methods. The GOHAI questionnaire with 6-level Likert scale, translated into Serbian, including the relevant oral health characteristics (oral hygiene, required dentures, number of teeth extracted), was filled by five specialists in prosthodontics for 30 randomly selected respondents, before and after the dental prosthetic treatment. Subsequently, in order to measure the reliability of the questionnaire, 27 patients were re-interviewed. Results. The value of Cronbach’s Alpha Coefficient (Crα) before the treatment was 0.878, and after the treatment it was 0.788 confirming the internal consistency and stability of the questionnaire. The validity of discriminatory properties of the GOHAI was confirmed by the Spearman’s correlation coefficient (r), which was highly significantly associated with oral health characteristics, confirming the high reliability of the measurement. The results of test-retest analysis measured by the individual Pearson’s correlation coefficient (r) were in the range of 0.34–0.97, and for the total score r was 0.927, while the Kappa coefficient was 0.63. The correlation analysis of the GOHAI score before the treatment showed that for 10 questions there was a statistically significant correlation of the score with the answers to the questions, and for 6 questions Spearman’s r was ≥ 0.7. After the treatment a highly significant correlation of the GOHAI was shown with the answers to 10 questions, while for 5 questions the Spearman’s r was > 0.6. The GOHAI average score before the treatment was 19.44 ± 11.12, and after the treatment 2.77 ± 3.83, where the lower value indicates better quality of life. Conclusion. The results of this pilot study confirm internal consistency and stability of the Serbian preliminary version of the GOHAI questionnaire and the causal relation between the quality of life and the characteristics of oral health of the patients with dentures. Accordingly, instrument verification is recommended. Key words: dentures; aged; questionnaires; quality of life; serbia.